Adventitious root primordia formation and development in the stem of Ananas comosus var. bracteatus slip. (2nd November 2021) - Owusu Adjei, Mark; Xiang, Yixuan; He, Yehua; Zhou, Xuzixin; Mao, Meiqin; Liu, Jiawen; Hu, Hao; Luo, Jiaheng; Zhang, Huiling; Feng, Lijun; Yang, Wei; Li, Xi; et al.
ABSTRACT: There are about 4–6 slips on a fruit, and they are good materials for effective regeneration of Ananas comosus var. bracteatus . Adventitious root (AR) induction is essential for the propagation of Ananas comosus var. bracteatus slips. Growth regulator treatment, and culture medium are imperative factors that affect slip growth and rooting. In order to screen the optimal methods for slips rooting and reveal the anatomic procedure of slip rooting, this study induced slip rooting by different treatment of growth regulator, culture medium, observed the slip stem structure, AR origination and formation procedure through paraffin sections. The results showed that, slip cuttings treated with 100 mg/L of Aminobenzotriazole (ABT) for 6 hrs, cultured in river sand: coconut chaff: garden soil 2:2:1 medium is the optimal method for rooting. The proper supplementary of ABT can enhance the soluble sugar content, soluble protein content, polyphenol oxidase (PPO) activity and peroxidase (POD) enzyme activity, which resulted in the improvement of rooting. The slip stem structure is quite different from other monocots, which consists of epidermis, cortex, and stele with vascular tissues distributed in the cortex and stele. The AR primordia originates from the parenchyma cells located on the borderline between the cortex and stele. The vascular tissues in the AR develop and are connected with vascular tissue of the stem before the AR grew out the stem. The number of primary xylem poles in AR is about 30.